1992
DOI: 10.1136/bmj.304.6819.91
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial of minocycline in lepromatous leprosy.

Abstract: indicates that about 2540 men in the sentenced prison population injected drugs in the six months before arrest.45 If we assume from our data that 8% of them were HIV positive that gives an estimated total of 203 HIV Patients, methods, and results Eight consenting adults (seven men and one woman) with lepromatous leprosy (five patients) or borderline lepromatous leprosy (three) who had been previously untreated (six) or whose leprosy had relapsed (two) were treated with 100 mg minocycline alone once daily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 4 publications
2
17
0
2
Order By: Relevance
“…Regarding mouse footpad infectivity, the activity of fusidic acid appears more similar to that of dapsone (20), a drug which is considered weakly bactericidal or bacteriostatic, than to the activities of more rapidly bactericidal drugs like rifampin (20), ofloxacin (16), minocycline (12), sparfloxacin (3), or clarithromycin (4). We unfortunately did not include a biopsy at 12 weeks which may have allowed a better comparison between fusidic acid and dapsone as well as between the two dosage groups.…”
mentioning
confidence: 99%
“…Regarding mouse footpad infectivity, the activity of fusidic acid appears more similar to that of dapsone (20), a drug which is considered weakly bactericidal or bacteriostatic, than to the activities of more rapidly bactericidal drugs like rifampin (20), ofloxacin (16), minocycline (12), sparfloxacin (3), or clarithromycin (4). We unfortunately did not include a biopsy at 12 weeks which may have allowed a better comparison between fusidic acid and dapsone as well as between the two dosage groups.…”
mentioning
confidence: 99%
“…16 Based on a clinical study in rats, showed that less M. leprae live in rats who received minocycline compared to rats who received dapsone dan clofazimin. 17 Despite having a strong bactericidal property, ROM regimen also has lesser side effects compared to MDT-WHO regimen. Several studies stated that ROM regimen side effects are less common to MDT-WHO which contains dapsone and clofazimin.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1-year WHO (37) regimen for MB leprosy, only rifampin (29,32,34), not dapsone (32) or clofazimine (32), is bactericidal for M. leprae in patients. Though pefloxacin/ofloxacin (9,19,26), minocycline (8,12), and clarithromycin (3) clear viable M. leprae bacilli in MB patients more rapidly than dapsone or clofazimine (32), in the Philippines, they do not result in significant killing following a single dose, and each requires a few months to reliably clear all viable M. leprae bacilli (3,8,9). On the other hand, in this present study, moxifloxacin was demonstrated to consistently result in killing of M. leprae in a single dose and to clear viable bacilli within days or weeks, similar to the rate previously demonstrated only by rifampin (29,32,34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the heavily infected, neonatally thymectomized Lewis rat, the combination of rifampin and ofloxacin was more regularly sterilizing than the combinations of both rifampin plus dapsone and rifampin plus clofazimine (10), rifampin, dapsone, and clofazimine being the three components of the widely implemented WHO-recommended regimens for treatment of multibacillary (MB) leprosy (36,37). Clinical trials of pefloxacin and ofloxacin treatments in leprosy have demonstrated encouraging clinical responses and the clearance of viable M. leprae within 2 months (9,19,26), this rate of clearance being higher than those with dapsone and clofazimine (several months [32]), similar to those with minocycline (8,12) and clarithromycin (3), but much lower than that with rifampin (29,32,34).…”
mentioning
confidence: 98%